Model Pembelajaran Project Citizen Sebagai Inovasi Pembelajaran Dalam Meningkatkan Keterampilan Abad 21 - Iwan Fajri; Rusli Yusuf; Mohd Zailani Mohd Yusoff (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English: In the current digital Era, it has a fairly broad impact in various aspects of human life, including in the life of the education sector, which demands for the implementation of educational institutions to carry out in accordance with the times. One of the real challenges for educational institutions should be able to produce human resources who have complete competence, known as 21st century competencies or skills. 21st century skills are the main skills that must be possessed by students in order to be able to take part in real life in 21st century. In the 21st century, educational institutions are challenged to be able to create and produce thinkers who are able to participate in building a social and economic order that is aware of knowledge as citizens of the world in the 21st Century. In the 21st century, they have several skills which include 1) Learning and innovation skills, 2 ) skills in using technology and information media and 3) life and career skills. To be able to improve 21st century skills in students, an effort is needed that can be applied to teaching and learning activities and one of the recommendations for learning innovation is through the application of the project citizen model. Project citizen learning is a problem-based and portfolio-based learning, through this model students are not only invited to understand scientific concepts and principles, but also develop their ability to work cooperatively, innovatively, creatively, and critically through empirical practice learning activities. (experience). Thus the learning process will be more challenging, active and more meaningful. The purpose of implementing this project citizen learning model is to be able to develop and improve 21st century skills through problem-based and portfolio-based learning processes. Bahasa: Di Era digital saat ini memberikan dampak yang cukup luas dalam berbagai aspek kehidupan manusia, termasuk dalam kehidupan dunia pendidikan, yang menuntut penyelenggaraan lembaga pendidikan agar berjalan sesuai dengan perkembangan zaman. Salah satu tantangan nyata bagi lembaga pendidikan harus mampu menghasilkan sumber daya manusia yang memiliki kompetensi lengkap, yang dikenal dengan kompetensi atau keterampilan abad 21. Keterampilan abad 21 merupakan keterampilan utama yang harus dimiliki siswa agar dapat berkiprah dalam kehidupan nyata di abad 21. Pada abad 21, mereka memiliki beberapa keterampilan yang meliputi 1) keterampilan belajar dan inovasi, 2) keterampilan dalam menggunakan teknologi dan media informasi dan 3) keterampilan hidup dan karir. Untuk dapat meningkatkan keterampilan abad 21 pada siswa diperlukan suatu upaya yang dapat diterapkan dalam kegiatan belajar mengajar dan salah satu rekomendasi inovasi pembelajaran adalah melalui penerapan model project citizen. Project citizen adalah pembelajaran berbasis masalah dan berbasis portofolio, melalui model ini siswa tidak hanya diajak untuk memahami konsep dan prinsip ilmiah, tetapi juga mengembangkan kemampuannya untuk bekerja secara kooperatif, inovatif, kreatif, dan kritis melalui kegiatan pembelajaran praktik empiris. (pengalaman). Dengan demikian proses pembelajaran akan lebih menantang, aktif dan lebih bermakna. Tujuan penerapan model project citizen ini adalah untuk dapat mengembangkan dan meningkatkan keterampilan abad 21 melalui proses pembelajaran berbasis masalah dan berbasis portofolio.